The properties and antecedents of hedonic decline. [article]. - Galak, Jeff.
We review the phenomenon of hedonic decline, whereby repeated exposure to a stimulus typically reduces the hedonic response (e.g., enjoyment). We first discuss the typical trajectory of hedonic decline and the common research paradigms used to study it. We next discuss the most popular theories regarding general mechanisms widely believed to underlie hedonic decline. We then propose a taxonomy to organize these various general theories and to incorporate more recent work on top-down, self-reflective theories. This taxonomy identifies three general classes of antecedents to hedonic decline: physiological feedback, perceptual changes, and self-reflection. For each class, we review the supporting evidence for specifically identified antecedents and recent developments on how each antecedent influences hedonic decline. Our review focuses especially on more recent work in the growing area of self-reflection. -- (from the author)
Keywords: Hedonic decline; Satiation; Satiety; Habituation; Hedonic adaptation; Enjoyment